Sosialisasi Bencana Geologi dan Mitigasinya di Sekolah Dasar Islam Terpadu (SDIT) Ar-Rahmah Makassar - Meutia Farida; Ilham Alimuddin; Adi Maulana; Ulva Ria Irfan; Asri Jaya; Sultan -; Kaharuddin -; Agustinus - (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2019)
Disaster-prone conditions in Indonesia cause a large number of impacts experienced such as casualties, damage to infrastructure and other vital facilities. With this impact, people's knowledge and understanding of geological natural disasters and mitigation efforts need to be educated early on. Mitigation is a series of activities carried out to reduce disaster risk and is included in the initial stages of natural disaster management. Of course the activity of providing geological disaster information and its mitigation is one of our responsibilities as geologists in academia to provide knowledge and understanding to the community, and one of the targets is early childhood or elementary school students. The output of this activity is to increase the capacity of the community, especially elementary school students, to understand early on the importance of disaster mitigation in efforts to reduce or minimize losses due to geological disasters. This activity was carried out by lecturing and simulation methods of a number of geological disaster events, the introduction of prepared disaster bags including the introduction of K3 (Occupational, Safety and Health).